The master of institutional multiplicity? The shifting politics of regime survival, state-building and democratisation in Museveni's Uganda. Issue 4 (1st October 2016) - Golooba-Mutebi, Frederick; Hickey, Sam
ABSTRACT: Current understandings of regime survival in Uganda tend to over-emphasise the role of 'semi-authoritarian' and 'neopatrimonial' politics and neglect the extent to which the regime deploys alternative strategies of political rule that also involve 'soft' forms of power and formal elements of state-building. The regime's extensive deployment of 'soft' power includes President Museveni's responsiveness to popular concerns and fears and the careful management of political rivals. Meanwhile, certain pockets of bureaucratic effectiveness have played an important role in securing legitimacy amongst both the voters and international actors who help maintain the regime in power. Viewed in comparison to previous elections in Uganda, the 2016 presidential poll revealed the regime's ability to achieve a balance between the extensive deployment of both hard and soft forms of power and of both formal and informal strategies of rule. However, whilst this capacity to manage 'institutional multiplicity' has underpinned the regime's success in maintaining itself in power for over three decades, a closer understanding of how this balancing act is achieved helps expose the increasingly contradictory logics of regime survival, democratisation and state-building in Uganda.